PENERAPAN PRINSIP FIDUCIARY DUTY DIREKSI PERSEROAN TERBATAS TASPEN (PERSERO): Application Of The Fiduciary Duty Principle By The Directors Of Pt Taspen (Persero) - Muhammad Adrian Ilham Ramadhan; Dian Purnamasari (Faculty of Law, Universitas Trisakti, 2025)
This study analyzes how the management of PT. Taspen (Persero) aligns with the fiduciary duty principle by its board of directors. The research problems in this study are how the fiduciary duty principle is applied in managing PT. Taspen (Persero), and what legal consequences arise if the board of directors violates such duty. Within the framework of a national economy based on democratic economic principles, state-owned enterprises like PT. Taspen hold a strategic role in promoting public welfare. The legal research method used is normative legal research with a descriptive approach, examining primary legal materials such as Law No. 40 of 2007 on Limited Liability Companies and Law No. 19 of 2003 on State-Owned Enterprises, as well as relevant secondary legal materials. Based on the results of the discussion, it can be concluded that any breach of fiduciary duty by the board of directors may give rise to personal liability for corporate losses. Compliance with fiduciary duty is essential to maintain integrity and public trust in managing state-owned assets.